Investigation on various stator structure towards noise and vibration - Nurfaezah Abdullah; Kasrul Abdul Karim; Raja Nor Firdaus Raja Othman; Auzani Jidin; Tole Sutikno (Institute of Advanced Engineering and Science, 2023)
This research analyses the noise and vibration characteristics of permanent magnet motors (PMM) with the electromagnetic characteristics, with an emphasis on high-speed motor segmented closed slot stator. The interaction between the stator, rotor, and magnets can cause a vibration that results in the loud sound due to the high magnetic energy. Even if there aren't many vibrations to contend with, the fluctuation of motor vibrations causes more serious harm. The studies covered slotted stator, closed slot stator, and segmented with closed slot stator. The objective is to analyze the cogging torque relation towards vibration and the effect of natural frequency at steady-state behavior of the structure. ANSYS finite element analysis (FEA) is used to generate electromagnetic analysis performance whilst ANSYS mechanical used to simulate the modal and harmonic analysis at the stator tooth tips surface to define the structure when the steady-state condition under vibrational stimulation. Anticipation on this work shows, the lowest cogging torque produce less radiated sound. Thus, the result indicates the cogging torque profiles had good agreement with the equivalent radiated power level (ERPL) waterfall diagram.